2016
DOI: 10.1159/000448186
|View full text |Cite
|
Sign up to set email alerts
|

Biological Subtypes and Distant Relapse Pattern in Breast Cancer Patients After Curative Surgery (Study of Anatolian Society of Medical Oncology)

Abstract: Purpose: The aim of the study was to investigate the association between the molecular subtypes and patterns of relapse in breast cancer patients who had undergone curative surgery. Methods: We retrospectively evaluated 1,350 breast cancer patients with relapses after curative surgery between 1998 and 2012 from referral centers in Turkey. Patients were divided into 4 biological subtypes according to immunohistochemistry and grade: triple negative, HER2 overexpressing, luminal A and luminal B. Results: The perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
4
9
0
Order By: Relevance
“…Nevertheless, results from a single institution study (104 patients) showed that breast cancer subtypes were not associated with survival after liver metastases (18), which are less likely to be generalizable. Our data are consistent with some of the general trends reported in academic center-based retrospective studies (24,33,42). Importantly, given the potential referral bias and other biases that can be presented in academic center-based series, we confirmed in a population-based sample of patients with newly diagnosed breast cancer and liver metastases that a median survival of nearly 3 years after diagnosis is now achieved in patients with HR-positive HER2-positive tumors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, results from a single institution study (104 patients) showed that breast cancer subtypes were not associated with survival after liver metastases (18), which are less likely to be generalizable. Our data are consistent with some of the general trends reported in academic center-based retrospective studies (24,33,42). Importantly, given the potential referral bias and other biases that can be presented in academic center-based series, we confirmed in a population-based sample of patients with newly diagnosed breast cancer and liver metastases that a median survival of nearly 3 years after diagnosis is now achieved in patients with HR-positive HER2-positive tumors.…”
Section: Discussionsupporting
confidence: 89%
“…In a retrospective case-control study of 103 patients with metastatic breast cancer, Buonomo and colleagues (33) showed that HER2-positive subtypes had a stronger association with systemic spread (OR, 2.127; 95% CI, 1.2-3.8) than other subgroups. In a retrospective study of 1,350 patients from referral centers in Turkey, Kaplan and colleagues (24) indicated that liver was the most frequent site of first metastases among HER2-overexpressing patients. Besides, results from other two studies suggested that HER2-rich subtypes have a liver-homing (OR ¼ 2.99) characteristic (5,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this study revealed the subtype-based differential susceptibility to distant metastasis in the contemporary era of breast cancer treatment. Several previous reports have explored the subtype-related preferential sites of distant metastasis [16,[21][22][23][24][25][26]. However, their results were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, their results were inconsistent. Although a potential bone-seeking phenotype of luminal tumors has been suggested [21][22][23][24], some reports could not verify this tendency [16,25]. In the study by Sihto et al of 234 patients diagnosed with distant metastasis as the first site of failure, the authors found higher frequencies of liver (27.1%) and lung (22.9%) metastases in patients with HER2 tumors and higher frequencies of lung (20.8%) and brain (9.5%) metastases in patients with basal-like tumors [21].…”
Section: Discussionmentioning
confidence: 99%